Nurses’ Disaster Mitigation Competencies in Public Health Center during Pandemic Covid-19 - Husna, Cut; Jayanti, Afrida; Fithria, Fithria (Jurnal Perawat Indonesia, 2021)
Mitigation is an effort to reduce disaster risk through physical development, public awareness, and community capacity building in facing disaster. The public health center (Puskesmas) as a facility is the spearhead of individual and community health services, especially in disaster situations. Nurses as the frontline in providing health services are expected to have competence in dealing with disasters. Increased disaster mitigation for nurses could be done by understanding disaster risk, disease prevention, health promotion, and policy development and planning. This study aims to determine the nurses’ competencies in disaster mitigation in the public health center. This research is a descriptive explorative with a cross-sectional study design. The total sampling method was carried out at two Puskesmas totaling 42 respondents. Data collection using Google-form in a dichotomy scale developed by researchers totaling 23 questions adopted from ICN-WHO, 2009. The questionnaire tested reliability with Cronbach Alpha = 0.7. The results of the study showed that the nurse's disaster mitigation competencies were at a good level (54.8%). For the sub-scales understanding of disaster risk (47.6%), disease prevention (76.2%), health promotion (61.9%) and policy development and planning (35.7%) are good competencies. It is recommended to health workers and community health centers to improve disaster risk management by making policies and plans that are organized by involving across professions, sectors, and all components of society.